Prehospital Stroke Triage. (16th November 2021) - Ramos, Anna; Guerrero, Waldo R.; Pérez de la Ossa, Natalia
Abstract : Purpose of the Review: This article reviews prehospital organization in the treatment of acute stroke. Rapid access to an endovascular therapy (EVT) capable center and prehospital assessment of large vessel occlusion (LVO) are 2 important challenges in acute stroke therapy. This article emphasizes the use of transfer protocols to assure the prompt access of patients with an LVO to a comprehensive stroke center where EVT can be offered. Available prehospital clinical tools and novel technologies to identify LVO are also discussed. Moreover, different routing paradigms like first attention at a local stroke center ("drip and ship"), direct transfer of the patient to an endovascular center ("mothership"), transfer of the neurointerventional team to a local primary center ("drip and drive"), mobile stroke units, and prehospital management communication tools all aimed to improve connection and coordination between care levels are reviewed. Recent Findings: Local observational data and mathematical models suggest that implementing triage tools and bypass protocols may be an efficient solution. Ongoing randomized clinical trials comparing drip and ship vs mothership will elucidate which is the more effective routing protocol. Summary: Prehospital organization is critical in realizing maximum benefit from available therapies in acute stroke. The optimal transfer protocols directed to accelerate EVT are under study, and more accurate prehospital triage tools are needed. To improve care in the prehospital setting, efficient tools based on patient factors, local geography, and hospital capability are needed. These tools would optimally lead to individualized real-time decision-making.